Adaptation of the learning styles questionnaire in 4th, 5th grade high school students and university students of the first semester, in a pilot sample - Salazar Díaz, Susan (2012)
Descriptive-type research, carried out in a sample of 150 students in the 4th or 5th high school grade or the first semesters of university studies. The objective of the research was to determine the psychometric characteristics of Morey-Alonso’s questionnaire of learning styles adapted to Peru by Zavala. As a result of the research, 15 items in the original test were deleted, and reliable indices were found.